Identifikasi Bakteri Escherichia coli pada Sumur Gali Warga Dusun Penemung Kabupaten Sumbawa dalam Penyusunan Buku Petunjuk Praktikum Mikrobiologi - Layyina Annisa Syafar; Sri Nopita Primawati; Husnul Jannah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Dug well water remains a primary source for meeting the daily water needs of many communities. However, the quality of dug well water can be influenced by environmental sanitation conditions, creating a potential risk of contamination by fecal indicator bacteria such as Escherichia coli. This study aimed to identify the presence of Escherichia coli in dug well water used by residents of Penemung Hamlet, Simu Village, Sumbawa Regency, and to develop and validate a research-based microbiology laboratory manual. An exploratory descriptive method was employed, involving sampling from ten dug wells. Bacterial isolation was performed using Eosin Methylene Blue Agar (EMBA) medium, followed by colony morphology identification, Gram staining, and IMViC biochemical testing. The laboratory manual was developed using the 4D model (up to the